If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6n + 1 = 0 Reorder the terms: 1 + -6n = 0 Solving 1 + -6n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -6n = 0 + -1 -6n = 0 + -1 Combine like terms: 0 + -1 = -1 -6n = -1 Divide each side by '-6'. n = 0.1666666667 Simplifying n = 0.1666666667
| 9u-16=6u-4 | | x^2+8x+16=17 | | -3/5x=-12 | | 1800.5.25.1/2 | | A=(2x-3)5 | | -1/2(28) | | 88.4=.34*b | | -2.1x^2+988x+13723= | | 3=.30*b | | =2(x*2+5x-696) | | 3=11u-8u | | 5xsquare-12=0 | | t=974*7+13412 | | 5x^2-2(3x-4x^2)-x= | | 2x*7x^2= | | s^2=24-4s | | 6(b-2)-5b=-13+4 | | =2(x-24)(x+29) | | sin(tan-1(-5/12)) | | 4x-3x+15=10-5 | | 15=5x-6-4x | | 62x^2+18x=0 | | 158-89(632)= | | -2(4+2y)=16 | | Y=-8-76 | | 12+4x+5x^2=0 | | -3.5x=47.25 | | Y=-28-38 | | 4-2=3x+4 | | A=(4x+5)(7x-2) | | -3x+14=3 | | 9(y+3)= |